The sleeping giant - Robertson, David, 1977- (Robertson, David, 1977- Misewa saga, 2024)
"Eli, Morgan and Emily embark on their most dangerous mission yet, to save the kidnapped animal beings of Ministik and to ensure that these terrible deeds will never happen again. Accompanied by Arik and Mahihkan, as well as the remaining Bird Warriors, they journey across the Flatlands toward the Land of the Sleeping Giant, in search of a long-lost cave where the Green Stars are said to be. The valuable gems are rumored to have great power, which Eli and Morgan will need to overcome an evil they've not faced before. As they draw ever closer, Eli develops more of his powers and learns new revelations about his mother."--